PROCHLORPERAZINE IN ANXIETY - Nigam, Pranesh (Medknow Publications, 1985)
Seventy patients suffering from primary anxiety state were selected for this clinical trial. They were randomly assigned to Prochlorperazine (Group I) and other drugs eg., Chlordiapoxide etc. (Group II). Hamilton's anxiety scale was employed to rate the anxiety. With the 4 weeks of therapy there was significant fall in score in both the groups of patients but the fall in score is more in Group I cases as compared to Group II (t = 11.5, df= 68, P < 0.001). The reduction in score (less than 10) and clinical improvement (medium to optimal improvement) was significantly more and faster in Group I (85%) cases as compared to Group II (70%) cases (χ(2) = 5.225, df = 1, P < 0.02). The side effects were least in Group I cases. Prochlorperazine (Stemetil) has given a significant anxiolytic effect without adversly affecting the mental function. In the dosage used prochlorperazine was free from the side effects and can be effectively employed in the management of anxiety.